The Contribution of Internal Audit to the Enhancement of Corporate Governance - LAFLAFLI , Sabah; SAIDI , Charaf (Revue Internationale des Sciences de Gestion, 2025)
The governance concept has emerged in recent years as a modern part of new managerial practices. This is due to the financial scandals that have erupted in the United States within some of the world’s major corporations. Furthermore, internal auditing, as a new mechanism, has emerged to strengthen the governance system at both financial and managerial levels. Accordingly, the aim of this study is therefore to explore the causal effect of the internal audit function as a control and monitoring body in improving the governance system. The study is based on an assessment of the effect of the internal control and risk management system on improving organizational governance. To address our research topic, an exploratory approach to the literature on the link between internal audit and governance is implemented, enabling us to highlight the theoretical design of the research, via a theoretical conceptual model describing the link between the tools of the internal audit function (internal control and risk management) on the improvement of corporate governance.